2352. Increased on Childhood Recurrent Wheezing and Asthma After Respiratory Syncytial Viral (RSV) Infection in Full-Term Infants. (26th November 2018) - Mejias, Asuncion; Wu, Bingcao; Tandon, Neeta; Chow, Wing; Connolly, Nancy; Lakhotia, Sahil; Franco, Eduardo; Ramilo, Octavio
Abstract: Background: Studies suggest that RSV infection early in life is associated with the development of recurrent wheezing, yet, information on large population-based studies among US full-term healthy infants is incomplete. The objective of this study was to evaluate the risk of developing post-RSV recurrent wheezing/asthma during childhood among full-term infants in a US commercially insured population. Methods: Retrospective, observational study used data from Truven MarketScan Commercial Claims and Encounters Database (January 1, 2000–December 31, 2016) to identify full-term infants with and without a RSV diagnosis in the first year of life (RSV and non-RSV cohorts respectively). Infants were excluded if they had any of the following: prematurity (<37 weeks' gestation), low birth weight, small for gestational age, congenital heart or chronic lung disease, asthma or wheezing; or had received palivizumab. At least 2 years' continuous follow-up post birth was required throughout the ≤5-year follow-up period. RSV/non-RSV infants were 1:1 matched for gender, region and health plan type. Cumulative incidence of recurrent wheezing or asthma was identified by ICD-9/10 codes, through 1, 2, 3 and 4 years (Y)' post-index (1 year after birth) follow-up, and analyzed using conditional logistic regression. Results: Matched RSV/non-RSV pairs totaled 38, 494 (Y1), 25, 603 (Y2), 17, 429 (Y3), and 11, 921 (Y4) for the years' follow-up. Demographic characteristics, birth year and month were evenly represented between cohorts. Other infections during the perinatal period were more common in the RSV vs. the non-RSV cohort (5.4% vs. 3.2%; P < 0.0001), as were other respiratory conditions (5.8% vs. 2.6%; P < 0.0001), and antibiotic use (76.7% vs. 44.7%; P < 0.0001). Rates of influenza and pneumococcal vaccinations were comparable between cohorts. Cumulative incidence of recurrent wheezing or asthma in the RSV cohort was more than two-fold higher compared with the non-RSV cohort for each follow-up period ( P < 0.001) (Figure 1). Conclusion: Healthy, full-term, commercially insured children infected with RSV during the first year of life had from 2.2- to 3.6-fold increased risk of developing recurrent wheezing or asthma in the next 1–4 years. This reveals an important medical need for interventions targeting RSV infection in infants. Disclosures: A. Mejias, Janssen: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Abbvie: CME talks, Speaker honorarium. B. Wu, Janssen Scientific Affairs, LLC: Employee and Shareholder, Salary. N. Tandon, Janssen Scientific Affairs: Employee and Shareholder, Salary and stocks. W. Chow, Janssen Scientific Affairs, LLC: Employee and Shareholder, Salary and stocks. N. Connolly, Janssen Scientific Affairs, LLC: Employee and Shareholder, Salary and Stocks. S. Lakhotia, Janssen Scientific Affairs, LLC: Research Contractor, Fee for service. E. Franco, Janssen Scientific Affairs, LLC: Employee and Shareholder, Salary and stocks. O. Ramilo, Janssen Scientific Affairs, LLC: Consultant, Consulting fee.